DNA computing and table based data accessing in the cloud environment. (15th December 2020) - Namasudra, Suyel; Sharma, Suraj; Deka, Ganesh Chandra; Lorenz, Pascal
Abstract: The attractive benefits of cloud computing environment motivate Information Technology (IT) companies to move their IT infrastructure on the cloud server. In a cloud environment, companies must depend on the untrusted Cloud Service Provider (CSP), which raises data security issues due to the presence of numerous hackers and malicious users. Apart from data security, high searching time of data owner, high data accessing time and high system overheard are other issues during data accessing from the cloud environment. To solve all these issues, in this paper, a novel DNA based fast and secure data access control model has been introduced for the cloud environment. Here, the cloud service provider maintains a table for fast and efficient data accessing. In this proposed scheme, a long 1024-bit Deoxyribonucleic Acid (DNA) based password or secret key is used to encrypt users' confidential or personal data. Experimental results along with theoretical analysis prove the efficiency of the proposed model over the existing models.